A qualitative and quantitative examination of using positive consequences in the management of student behaviors in Kenyan schools. - Onyango, Pamela Awuor; Raburu, Pamela A.; Aloka, Peter J. O. (Scientific & Academic Publishing, 2016)
He challenge of addressing students’ behaviour problems in Kenya cannot be over emphasized. The present study investigated the effectiveness of positive reinforcement in the management of student behavior problems in public secondary schools in Kenya. Thorndike’s Behavior Modification theory informed the study. Mixed methods paradigm that had both quantitative and qualitative approaches was adopted, together with concurrent triangulation design. The study population comprised 380 teachers from a total number of 40 schools that had 40 Heads of Guidance and Counseling (HOD), 40 Deputy Principals (DP) and 300 classroom teachers. A sample size of 28 Deputy Principals, 28 Heads of Guidance and Counseling and 196 teachers were involved. Reliability of the instruments was ascertained by conducting a pilot study in 9% of the population that didn’t participate in the actual study. Face validity of the instruments was ensured by seeking expert judgment by university lecturers. Quantitative data were analyzed using descriptive statistics and inferential statistics while the qualitative data was analyzed using thematic framework. The study findings revealed that positive reinforcement was effective in managing student behavior problems. The study findings may be a source of intervention to the school administration in the management of escalating student behavior problems. The study recommended training of teachers on better modes of students’ behavior management.
Keywords: Effectiveness; Exclusion; Student; Behavior Problems